2021
DOI: 10.1088/2053-1591/ac0c50
|View full text |Cite
|
Sign up to set email alerts
|

A wrinkled ZnO/MCM-41 nanocomposite: hydrothermal synthesis and characterization

Abstract: ZnO/MCM-41 composites consisting of loose particles with an irregular, wrinkled surface and flower-like morphology were obtained by adding MCM-41 to a mixture of zinc nitrate hexahydrate and hexamethylenetetramine under hydrothermal conditions. The physical properties of this composite were determined by scanning electron microscopy (SEM), x-ray powder diffraction (XRD), Fourier Transform Infrared spectroscopy (FTIR), and photoluminescence spectroscopy (PL). The XRD analysis showed the characteristic diffracto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…For example, Burova et al reported the synthesis of ZnO nanoparticles in MCM-41, where ZnO nanoclusters between 5 and 35 nm were formed in the mesopores . A ZnO/MCM-41 nanocomposite was reported where the mesopores served as a template for the growth of ZnO nanoparticles. , In these examples, the 1D mesopores are filled with ZnO nanoparticles, which reduces the surface area. There have been several attempts to either coat nanoparticles with wrinkled silica layers or prepared core–shell silica composite. For example, Fe 3 O 4 nanoparticles were coated with dye-functional wrinkled silica for drug delivery .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Burova et al reported the synthesis of ZnO nanoparticles in MCM-41, where ZnO nanoclusters between 5 and 35 nm were formed in the mesopores . A ZnO/MCM-41 nanocomposite was reported where the mesopores served as a template for the growth of ZnO nanoparticles. , In these examples, the 1D mesopores are filled with ZnO nanoparticles, which reduces the surface area. There have been several attempts to either coat nanoparticles with wrinkled silica layers or prepared core–shell silica composite. For example, Fe 3 O 4 nanoparticles were coated with dye-functional wrinkled silica for drug delivery .…”
Section: Introductionmentioning
confidence: 99%
“…34 A ZnO/MCM-41 nanocomposite was reported where the mesopores served as a template for the growth of ZnO nanoparticles. 35,36 In these examples, the 1D mesopores are filled with ZnO nanoparticles, which reduces the surface area. There have been several attempts to either coat nanoparticles with wrinkled silica layers or prepared core−shell silica composite.…”
Section: ■ Introductionmentioning
confidence: 99%